A probabilistic seismic hazard model for Mainland China. Issue 1 (October 2020) - Rong, Yufang; Xu, Xiwei; Cheng, Jia; Chen, Guihua; Magistrale, Harold; Shen, Zheng-Kang
We construct a probabilistic seismic hazard model for mainland China by integrating historical earthquakes, active faults, and geodetic strain rates. We delineate large seismic source zones based on geologic and seismotectonic characteristics. For each source zone, a tapered Gutenberg–Richter (TGR) distribution is used to model the total seismic activity rates. The TGR a - and b -values are calculated using a new earthquake catalog, while corner magnitudes are constrained using the seismic moment rate inferred from a geodetic strain rate model. For hazard calculations, the total TGR distribution is split into two parts, with smaller ( MW  < 6.5) earthquakes being distributed within the zone using a smoothed seismicity method, and larger earthquakes put both onto active faults, based on fault slip rates and dimensions, and into the zone as background seismicity. We select ground motion models by performing residual analysis using ground motion recordings. Site amplifications are considered based on a site condition map developed using geology as a proxy. The resulting seismic hazard is consistent with the fifth-generation national seismic hazard model for most major cities.